Conceptual representation and the making of new decisions. - Boorman, E; Rushworth, M (2009)
A key feature of an adaptive decision making mechanism is its ability to guide behavior even in new situations. In this issue of Neuron, Kumaran et al. report that conceptual representations, which allow generalization from one situation to another through their shared features, can guide decisions even when new problems are encountered via the hippocampus.